ANALISIS TINGKAT KEMAHALAN HARGA, RETURN SAHAM, EPS DAN LIKUIDITAS PERDAGANGAN SAHAM TERHADAP KEPUTUSAN STOCK SPLIT - Devy Handayani, Ni Putu Pradnyamitha; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2017)
A stock split is an action undertaken by issuer to break down the original value of shares into the smaller ones in order to increase the number of shares in market without making any raising in the paid-up capital. This study aims to provide empirical evidences about analysis of the expensiveness level of price, stock returns, earning per share, and the liquidity of stock trades towards the stock split decision. The population is manufactured companies listed in Indonesian Stock Exchange 2013-2015. The sampling method using non-probability method with a purposive sampling technique obtained 129 company samples and 387 observational. The technique analyzing is discriminant analysis. The result of hypothesis testing shows that the variable of stock returns and earnings per shares give a positive impact to the stock split decision. On the other hand, the level of expensiveness price and the liquidity of the trades do not give such impact.
Keywords: Expensiveness Level of Price, Stock Returns, Earning Per Shares, Liquidity of the Stock Trades, Stock Split